Analisis Faktor-Faktor yang Mempengaruhi Kinerja Widyaiswara - Suwatno Suwatno; Marsudi ' (Universitas Riau, 2010)
BPG (Teacher Upgrading Center) is a technical and operational units that are structurallyunder the Directorate General of Primary and Secondary, where widyaiswara are the spearhead forthe performance of the organization. Given the strategic position, widyaiswara required a qualitythat capable to perform optimally in their roles and functions. The basic assumption is that therecruitment, selection, motivation, also education and training, have a significant influence on theperformance of Widyaiswara. The purpose of this study was to determine and analyze the influ-ence of recruitment, selection, motivation, also education and training, to widyaiswara perfor-mance at the Directorate General of Primary and Secondary.The method used in this research isdescriptive and explanatory survey, with techniques of survey for data collection, and question-naire form for research instruments. This research is study to 80 people of Widyaiswara at theDirectorate General of Primary and Secondary Jakarta. Data analysis technique used to examinationthe research hypothesis is using correlation and regression techniques.Based on research out-comes, obtained findings the influence of recruitment, selection, motivation, also education andtraining, to the widyaiswara performance at the Directorate General of Primary and SecondaryJakarta. Thus, it is necessary improvements and continuous optimization of the recruitment, selec-tion, motivation, also education and training, within the Directorate General of Primary and Second-ary Jakarta, to improve widyaiswara performance.